2022
DOI: 10.47360/1995-4484-2022-276-279
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid arthritis and post-COVID-19 syndrome

Abstract: In the third year of the SARS-CoV-2 (severe acute respiratory syndrome coronavirus-2, COVID-19) pandemic doctors are encountering a new pathology – post-COVID-19 syndrome (PCS, long covid). Musculoskeletal manifestations are among the most common and may present as myalgia, arthralgia, or arthritis. Currently, there is no generally accepted definition of the disease, its duration, classification, or diagnostic criteria, and no single view on the “content” of musculoskeletal manifestations of PCS. We have enoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…It can be hypothesized that COVID‐19 may also trigger some (autoimmune) rheumatic diseases. Such a hypothesis is now supported by numerous observations, including our own 25 . We now offer our scheme with several scenarios of arthritis post‐COVID‐19 (Box 2).…”
Section: Inflammatory Arthritis and Rheumatoid Arthritis (Ra) After S...supporting
confidence: 56%
See 1 more Smart Citation
“…It can be hypothesized that COVID‐19 may also trigger some (autoimmune) rheumatic diseases. Such a hypothesis is now supported by numerous observations, including our own 25 . We now offer our scheme with several scenarios of arthritis post‐COVID‐19 (Box 2).…”
Section: Inflammatory Arthritis and Rheumatoid Arthritis (Ra) After S...supporting
confidence: 56%
“…Such a hypothesis is now supported by numerous observations, including our own. 25 We now offer our scheme with several scenarios of arthritis post‐COVID‐19 (Box 2 ).…”
Section: Inflammatory Arthritis and Rheumatoid Arthritis (Ra) After S...mentioning
confidence: 99%
“…Back in 2020, we presented a hypothesis of COVID‐19 as a potential trigger of RA at the APLAR congress and published a related abstract in IJRD in October 2020. The same hypothesis, enriched with growing evidence, was discussed in our publication in 2022 4 . With time passing and accumulating evidence, similar hypotheses of COVID‐19‐induced RA were tested in large studies with crystallizing a scientific fact of the association.…”
mentioning
confidence: 73%
“…The same hypothesis, enriched with growing evidence, was discussed in our publication in 2022. 4 With time passing and accumulating evidence, similar hypotheses of COVID-19-induced RA were tested in large studies with crystallizing a scientific fact of the association. Indeed, cohort studies in Taiwan, Germany, the UK, and South Korea, published in 2023, confirmed that SARS-CoV-2 infection was associated with increased ARD morbidity.…”
Section: Increasing Autoimmune Rheumatic Diseases As a Consequence Of...mentioning
confidence: 99%
See 1 more Smart Citation